1991
DOI: 10.1111/j.1365-2621.1991.tb01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to modified atmosphere packaging for extending the shelf‐life of partly ripened Doyenné du Comice pears

Abstract: Although some retardation in ripening of Doyenne du Comice pears can be obtained when unripe fruit are held in modified atmosphere packs (MA) at 20"C, softening proceeds at a faster rate than chlorophyll loss so that the appearance of the fruit fails to match its internal condition. However, a 4-day extension in shelf-life was obtained by packing the fruit in a part-ripe condition and, although the effects on rate of softening were less than those seen for unripe fruit, the yellower ground colour was more cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Other researchers (Smith et al. 1989; Geeson et al. 1991b) indicate that problems can occur with the use of MAP and fruit, particularly injury in “Comice” and “Conference” pears.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers (Smith et al. 1989; Geeson et al. 1991b) indicate that problems can occur with the use of MAP and fruit, particularly injury in “Comice” and “Conference” pears.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators report benefits on quality (firmness retention, reduced physiological disorders) in fruits with extended shelf life (Hewett and Thompson 1988;Geeson et al 1991a;Zoffoli et al 2002). Other researchers (Smith et al 1989;Geeson et al 1991b) indicate that problems can occur with the use of MAP and fruit, particularly injury in "Comice" and "Conference" pears. Hansen (2001) reported that MAP of "Bartlett" pears helped maintain quality, but that the risk of internal injury can be magnified with this type of package.…”
Section: Introductionmentioning
confidence: 99%